Targeting BET proteins inhibited the growth of non‐small cell lung carcinoma through downregulation of Met expression. (30th November 2022) - Yuan, Ting; Ni, Ping; Zhang, Zuhao; Wu, Dandan; Sun, Geng; Zhang, Haijun; Chen, Baoan; Wang, Xuerong; Cheng, Zhixiang
Abstract: Hepatocyte growth factor receptor (HGFR or Met) upregulation has been proven to play important roles in non‐small cell lung carcinoma (NSCLC). Interestingly, chemoresistance against epidermal growth factor receptor (EGFR) inhibitors including erlotinib and gefitinib was also related to Met. Targeting bromodomain and extra terminal domain (BET) proteins, especially BRD4, has shown inhibitory effects on lung cancer, but the mechanism is unclear. Herein, we found that JQ1 (BET inhibitor) suppressed NSCLC cell growth, reduced the Met expression, and contributed to inactivation of PI3K/Akt and MAPK/ERK pathways. Moreover, another BET protein inhibitor I‐BET151, or BRD4 depletion, also inhibited NSCLC cell growth and downregulated Met. JQ1 inhibited HGF‐induced cell growth and Met/PI3K/Akt activation, also inhibited A549 tumor growth in xenograft mouse models, in parallel with Met downregulation. Moreover, JQ1 inhibited the growth of paired erlotinib‐sensitive and resistant HCC827 cells in parallel with Met downregulation and PI3K/Akt signaling inactivation. JQ1 also exerted inhibitory influences on the growth of erlotinib‐sensitive and resistant HCC827 tumors in xenograft mouse models. These results suggested that targeting BET proteins inhibited NSCLC via downregulating Met and inactivating PI3K/AKT pathway. Our findings reveal a novel mechanism of BET proteins implicated in NSCLC progression with Met taken into consideration.